Analysis of the Effect of the Quality of Financial Statements on Investment Decisions - Conny Santosa (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates the analysis of the effect of the quality of financial statements on investment decisions among manufacturing firms listed on the Indonesia Stock Exchange between 2020-2022. Grounded in agency theory, the research addresses the persistent issue of investment inefficiency and the mixed empirical evidence surrounding financial reporting. Using a quantitative approach and purposive sampling, data were gathered from 114 firm-year observations and analyzed through multiple linear regression. The empirical results demonstrate that profitability exerts a positive and statistically significant effect on investment decisions, highlighting the critical role of operational efficiency in resource allocation. However, the quality of financial statements does not show a statistically significant effect on investment decisions within the observed sample, indicating that financial disclosure quality alone may not be the primary driver of investment decisions in this context. These findings offer practical implications for corporate managers, investors, and policymakers, suggesting that while transparency is essential, operational profitability remains a more decisive factor in effective investment outcomes.